2018 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD) 2018
DOI: 10.1109/itmc.2018.8691131
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Sustainable Demand Chain Framework: Successful Product Development Integration and Drivers

Abstract: The study seeks to fulfil the ultimate step of the previous researches on demand chain concepts within manufacturing environments, with a specific focus on sustainability criteria. In this case, New Product Development (NPD), Industry 4.0 and smart manufacturing act as effective tools towards production of updated products facilitating both business survivability and customer satisfaction. This paper utilizes a brief overview of the literature studies as a knowledge platform and further investigates the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For instance, Bala and Verma [20] indicated that the internet has significantly contributed to the transition towards market-driven marketing approaches that involve formalized techniques of acquiring accurate and timely information regarding customers, the market, products, and the general business environment. The internet allows marketers to utilize electronic commerce (e-commerce) to sell and market products and services online [21]. The history of internet-based marketing dates back to 1990, when people began using websites to provide customers with product information.…”
Section: Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Bala and Verma [20] indicated that the internet has significantly contributed to the transition towards market-driven marketing approaches that involve formalized techniques of acquiring accurate and timely information regarding customers, the market, products, and the general business environment. The internet allows marketers to utilize electronic commerce (e-commerce) to sell and market products and services online [21]. The history of internet-based marketing dates back to 1990, when people began using websites to provide customers with product information.…”
Section: Marketingmentioning
confidence: 99%
“…The thematic areas covered by the 61 scientific and/or academic documents were: Business, Management and Accounting (61); Decision Sciences (21); Engineering (15); Economics, Econometrics and Finance (11); Computer Science (10); Social Sciences (six); Mathematics (three); Psychology (two); and one each for the remaining keywords (Arts and Humanities, Energy, Environmental Sciences, Medicine, and Physics and Astronomy).…”
Section: Literature Analysis: Themes and Trendsmentioning
confidence: 99%
“…For instance, Bala and Bala and Verma [29] indicate that the internet has significantly contributed to the transition towards market-driven marketing approaches that involve formalized techniques of acquiring accurate and timely information regarding customers, the market, products, and the general business environment. The internet allows marketers to utilize electronic commerce (e-commerce) to sell and market products and services online [30]. The history of internet-based marketing dates back to 1990 when people began using websites to provide customers with product information.…”
Section: Marketingmentioning
confidence: 99%
“…The central idea of Industry 4.0 is the trend of digitization, automation, and increased use of information and communications technology (ICT) [18]. People's lives and workplaces are radically changing as a result of the digital revolution, but the public is nevertheless hopeful about the prospects that Industry 4.0 may present for sustainability [19]. These technologies are eventually anticipated to jointly determine Industry 4.0's success.…”
Section: Overview Of Marketing Strategies 40mentioning
confidence: 99%